Rural Prenatal Care by Nurse Practitioners: A Narrative Review - Monica Kneller; Edith Pituskin; Nicole L. Tegg; Colleen M. Norris (Mary Ann Liebert, 2023)
Background: Rural Canadian populations face many challenges due to their geographical isolation, including inaccessible and inequitable primary health care. Specifically, pregnant women are at risk of not receiving prenatal care (PNC) due to physical and social barriers. Inadequate PNC can have detrimental effects on both maternal and neonatal health outcomes. Nurse practitioners (NPs) are an essential group of alternative primary care providers who can provide specialized care, including PNC, to these underserved populations. Objective: The purpose of this narrative review was to identify existing NP-led rural PNC programs in other health care systems to support maternal and neonatal outcomes. Methods: A systematic search was performed to identify articles published between 2002 and 2022 on CINAHL (EBSCO host) and MEDLINE (OVID). Literature was excluded if (1) the context was based in urban centers; (2) the study focused on specialized obstetrical/gynecological-based care; or (3) the study was published in a language other than English. The literature was assessed and synthesized into a narrative review. Results: The initial search identified 34 potentially relevant articles. Five broad themes were identified, including (1) barriers to care; (2) mobile health clinics; (3) collaborative or tiered models of care; (4) telemedicine; and (5) NPs as essential primary care providers. Conclusions: The introduction of a collaborative NP-led approach to rural Canadian settings has the potential to address barriers to PNC and provide efficient, equitable, and inclusive health care.